Reducing process costs with lean, six sigma, and value engineering techniques - Pries, Kim H., 1955- (CRC Press, 2013)
A company with effective cost reduction activities in place will be better positioned to adapt to shifting economic conditions. In fact, it can make the difference between organizations that thrive and those that simply survive during times of economic uncertainty. Reducing Process Costs with Lean, Six Sigma, and Value Engineering Techniques covers the methods and techniques currently available for lowering the costs of products, processes, and services. Describing why cost reductions can be just as powerful as revenue increases, the book arms readers with the.